Biomechanical model predicts directional tuning of spindles in finger muscles facilitates precision pinch and power grasp - Horch, James Biggs, Kenneth (Somatosensory & motor research, 1999)
Humans have a sense of static limb position derived primarily from the output of secondary muscle spindle endings. The features of finger pose these proprioceptors signal best were predicted by singular value decomposition of a kinematic model of the human long finger and the six muscles that actuate it. The analysis indicated that muscle spindles signal the location of the fingertip with less error than they signal angles of individual finger joints. The fingertip displacements for which proprioceptors have greatest sensitivity were also predicted. These fingertip displacements seem to correspond to the fine positioning of an object pinched between the fingertip and distal phalanx of the thumb. The analysis also predicted the directions in which subjects can displace the fingertip most rapidly. The directions seem to correspond to rapid closure of precision pinch or power grasp.